Lords of Quibbitt - "Collins, Paul"; "Willis, Danny " (Rowville, Vic; Five Mile Press, 2008)
The next captivating fantasy title in the popular The World of Grrym series."--Provided by publisher
Keywords: English Fiction-Fantacy